Leitura compartilhada por professores para ampliação das interações comunicativas e linguagens em crianças - Menotti, Ana Rubia Saes (2020)
During childhood language difficulties have been identified as a risk factor for social and academic development. Shared story reading plays an important role in promoting the language. The general objective of this thesis was to evaluate the effect of an intervention program applied by teachers to expand vocabulary and the number of conversations initiated by children in Early Childhood Education, inserted in regions with low socioeconomic status. The thesis had its secondary objective to systematically evaluate the possible effects of this intervention on the acquisition of written language. The work was organized in two studies. Study 1 aimed at verifying the effects of continuing formation with teachers of early childhood education, which should put into specific strategies during shared reading, stimulation of children's oral language and the generalization of these strategies in other daily activities. Study 2, with the general objective of verifying the impact that the continuing formation performed with the teachers in Study 1 had on the development of the children's oral and written language, considering that the teachers started to use more consistently in their classrooms some strategies that they are considered by the literature as efficient for oral language promotion in the school context. The intervention performed in Study 1 showed evidence of changes in teachers' practices, especially in times of shared reading (Study 1), but this result was not enough to verify the increase in oral and written language competence of children who were inserted in the classroom of the teachers participating in the training (Study 2). We discuss the need for refinement of the instruments used to assess children's language competence and also for more lasting and continuous interventions throughout early childhood education.